A Slam-dependent hemophore contributes to heme acquisition in the bacterial pathogen Acinetobacter baumannii - Thomas J. Bateman (Nature Portfolio, 2021)
Nutrient acquisition is crucial for the growth of pathogens within their hosts. Here, Bateman et al. identify a set of proteins required for heme uptake from host hemoglobin and serum albumin in the pathogen Acinetobacter baumannii.